Sighhh…. hard snaps, but that's the way it is / Nor Elyzatul Akma Hamdan - Hamdan, Nor Elyzatul Akma (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.